Evaluation Of Tannin From Rhizophora Apiculata As Rust Converter - SANTOSO, HENNY SUMILO (2005)

(untitled)
The main objective of this research is to formulate rust C<?nverter formulations based on tannin and to evaluate their rust conversion performance. The tannins that were used in this study were extracted from mangrove (Rhizophora apiculata) barks which are the waste product from charcoal industry. The extraction of mangrove bark with 70 % aqueous acetone produced 23.6 % mixed tannin, which contained 12.3 % hydrolysable tannin and 8.7 % condensed tannin. The quantifications of tannin have been carried out by several assays, such as Prussian blue assay for total phenolic determination; vanillin assay to estimate condensed tannin, Stiasny test to provide the estimation of the total flavanoid that react with formaldehyde.